The Psychometric Properties of a Modified Sit-to-Stand Test With Use of the Upper Extremities in Institutionalized Older Adults. Issue 1 (August 2016) - Le Berre, Melanie; Apap, David; Babcock, Jade; Bray, Sarah; Gareau, Esther; Chassé, Kathleen; Lévesque, Nicole; Robbins, Shawn M.
Current sit-to-stand protocols do not permit use of upper extremities, limiting the protocols' utility for institutionalized older adults with diminished physical function. The objective of this study was to modify a 30-s sit-to-stand protocol to allow for arm use and to examine test–retest reliability and convergent validity; 54 institutionalized older adult men (age = 91 ± 3 year) performed the 30-s sit-to-stand twice within a span of 3 to 7 days. Results suggest good test–retest reliability (intraclass correlation coefficient = .84) and convergent validity with the Timed Up and Go Test ( r = −.62). This modified 30-s sit-to-stand can be used to assess physical function performance in institutionalized older adults and will ensure that individuals with lower physical function capacity can complete the test, thus eliminating the floor effect demonstrated with other sit-to-stand protocols.